Aplikasi Augmented Reality Gerakan Dan Bacaan Sholat Berbasis Android - Puji Pambudi; Dimas Abisono Punkastyo (CV. Multi Kreasi Media, 2023)
Technological advances are growing rapidly, especially on Android-based gadgets/smartphones. With the development of Android, there are many applications that have an effect on helping the learning process in schools and also have an effect on learning materials and how to be aware of material in the teaching and learning process, one of which is the Augmented Reality application. Augmented Reality (3D) is an application that combines the real world with the virtual world in a three-dimensional form that is projected in a real environment at the same time. This research to help expedite the teaching process in schools in understanding subject matter, especially in learning prayer movements and readings. The Augemnted Reality application is expected can be used as a learning media to help teachers in the learning process and is also able to make it easier for children to remember prayer movements and readings. By using the Waterfall method, structured planning is formed and development is carried out sequentially and mutually sequentially in making Augmented Reality Applications. From the results of research on the Augmented Reality application with the Waterfall method after testing the teacher and children, the results obtained on the display of 3D objects help make it easier for children to learn movement and prayer readings and this application can be applied every day at Tahfidz School Friends of Early Childhood Qur'an Mutiara Hasanah